Recent and episodic activity of decoupled mud/fluid discharge at Sartori mud volcano in the Calabrian Arc, Mediterranean Sea - Doll, Mechthild; Römer, Miriam; Pape, Thomas; Kölling, Martin; Kaul, Norbert; dos Santos Ferreira, Christian; Bohrmann, Gerhard (Frontiers in Earth Science, 2023)
Mud volcanoes (MVs) are surface structures typically created by episodic discharge of fluids and solids often associated to onshore and offshore accretionary prisms on convergent plate boundaries. Detailed investigations of ongoing activity and its associated morphological changes, as well as a better understanding of the temporal evolution of these highly dynamic systems may improve estimations of material fluxes from MVs drastically. Until today, about 70 individual MVs were are discovered from the northern Ionian Sea in the Calabrian Arc (Central Mediterranean Sea) but only a few are have been analyzed and described in detail. In this study, new evidence for recent recurring eruptive activity of the ~45 m high and 1 km wide Sartori MV situated in the clastic wedge of the Calabrian Arc is presented. High-resolution seafloor mapping as well as sediment temperatures, geochemical and sedimentological data received from two research cruises in 2016 and 2020 are used. Bathymetric and backscatter data (1m-scale) indicate the presence of two active eruption centers at the flat-topped Sartori MV. Elevated sediment temperature gradients at both eruption centers show that currently heat is transferred to the surface sediments. Pore water analyses indicate fluids rising below the eruption centers are CH4-rich, Cl --poor and SO4 2--free. Stable C and H isotopic compositions of methane suggest that it originates from a mix of primary microbial, secondary microbial, and/or thermogenic sources. A relatively shallow position of the sulfate-methane interface at both eruption centers also indicate the presence of upward fluid migration in recent times. Pore water modelling suggests that seawater has penetrated the surface sediments to a greater extent within the last few years. In contrast, cm-thick layers of hemipelagic sediments overlying mud breccia in sediment cores taken from both eruption centers show that no solid material has been ejected in recent times. Sediment core analyses combined with high-resolution seafloor mapping show an absence of rim-passing mudflows over the past ~10 ka. It is concluded that Sartori MV is an episodically active MV from which fluids with a comparatively low flux were released into the bottom water in recent times.